Da objetividade do risco à subjetividade da sua percepção: dimensões do risco socioambiental no Jardim Kennedy em Poços de Caldas, MG - Nathália Mariane Francisco (2024)
The research aims to investigate the objective and subjective dimensions of socio- environmental risk in the case of Jardim Kennedy, in Poços de Caldas, MG. Jardim Kennedy is a neighborhood located on the outskirts of the city, where low-income families reside and where it is possible to observe socio-political processes that exacerbate the vulnerability of the local population. The neighborhood is mapped by three distinct "flood inundation zones." The first is related to the hydrological risk associated with rainy events. The second is related to the dam break study of the Alcoa Alumínio S.A. dams, a company that operates bauxite mines and processes the ore for aluminum production. The third "flood inundation zone" comes from the dam break studies of the Cipó water reservoir dam. In addition to being affected by successive floods and inundations during rainy periods, the population is also registered in two Self-Rescue Zones (ZAS) for being downstream of the Alcoa and Cipó dams. The overlap between poverty and more than one type of risk aligns with the denunciations made by studies on Political Ecology and Environmental Justice regarding inequities in the distribution of socio- environmental risk. In view of the above, we will discuss the different forms of conception and apprehension of socio-environmental risk in Jardim Kennedy among the so-called specialists (technicians) and non-specialists (residents).